Ethnicity and Credit in African Manufacturing. - Fafchamps, M (2000)
This paper investigates whether market interaction can, by itself, perpetuate the lack of ethnic diversity that is observed in the business communities of many developing countries. Using case study data on manufacturing firms in Kenya and Zimbabwe, we find no evidence that blacks or women are disadvantaged in the attribution of bank credit once we control for firm size and other observable characteristics. In contrast, an ethnic and gender bias is noticeable in the attribution of supplier credit. Although we cannot rule out the presence of discrimination, the bulk of the evidence indicates that network effects play an important role in explaining this bias.